Against all odds: Job search during the Great Recession - Gustavo Leyva (Banco de México, 2018)
The unemployed in the United States appear to allocate time to job search activities regardless of the stance of the economy. Drawing on the American Time Use Survey between 2003 and 2014, I document that the unemployed increase their search intensity only slightly if at all during recessions. Roughly, 30 minutes in a week is the additional search intensity attributed to the unemployed in response to the Great Recession. While their search intensity depends on a number of factors that would predict otherwise, such as the odds of finding work, one argument shows promise: the search costs that accumulate over an expected long period of unemployment make a job more valuable during recessions. I estimate the elasticity of the value of a job to changes in labor productivity to be at least - 0.67 and at most -0.04.
Keywords: E24; E32; J22; J64; 330; unemployed; search intensity; value of a job; business cycle